2017
DOI: 10.1016/j.jcrs.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and patient satisfaction 3 and 12 months after implantation of a refractive rotationally asymmetric multifocal intraocular lens

Abstract: This asymmetric multifocal IOL provided excellent unaided vision with no significant difference in near, intermediate, and distance vision 3 months and 12 months postoperatively. However, there was a significant improvement in subjective outcomes at the second postoperative assessment, during which patients reported a significantly better QoV score and less blurred vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
4
13
1
4
Order By: Relevance
“…At both postoperative assessments, the majority of patients in both groups reported excellent spectacle independency. McNeely et al [23] found that 100.0% of patients never used spectacles, which is similar to the results in our study. Moreover, a limitation of our study is absence of data on various visual disturbances and photopic phenomena, which should be evaluated in future prospective studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At both postoperative assessments, the majority of patients in both groups reported excellent spectacle independency. McNeely et al [23] found that 100.0% of patients never used spectacles, which is similar to the results in our study. Moreover, a limitation of our study is absence of data on various visual disturbances and photopic phenomena, which should be evaluated in future prospective studies.…”
Section: Discussionsupporting
confidence: 93%
“…SBL-3 is the second commercially available model of MIOL based on the concept of rotationally asymmetric. Several studies have shown that this MIOL provided excellent vision outcomes with a good range of functional vision [23]. e present study sought to compare the far, near, and intermediate visual acuity outcomes, defocus curve, and intraocular optical quality parameters in patients with SBL-3 and SN6AD1.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that there is a period of neuroadaptation with multifocal IOLs during which visual symptoms appear to subside and overall patient satisfaction increases. 8 This is in agreement with a study by McNeely et al 9 that assessed the SBL-3 IOL 3 and 12 months postoperatively to determine overall patient satisfaction. The study found that the overall quality of vision improved from 3 to 12 months postoperatively despite no statistically significant change in objective visual or refractive outcomes.…”
Section: Conclusion: Both Refractive Rotationally Asymmetric Multifocalsupporting
confidence: 88%
“…The SBL-3 has been clinically used to improve intermediate vision and reduce visual disturbances while restoring good visual outcomes at near and distance. 4 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%